Instructional Design for Teaching Manṣūbāt al-Asmā' Based on the Pyramid Theory at the Madrasah Aliyah - Rahmawati, Neli Dian; Inayah, Inayah; Siddiq, Mahfudz; Al Aufa, Muhammad Miftah (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This article aims to design instructional materials for teaching manṣūbāt al-asmā' based on the Pyramid Theory at the MA level. The method employed is descriptive-analytical, using a library research approach and drawing on classical nahwu texts and contemporary Arabic language education literature. The data comprise primary sources (the classical nahwu texts Jāmi' al-Durūs al-'Arabiyyah, Al-Ājurrūmiyyah, al-Imriṭī, and Alfiyyah Ibn Mālik) and secondary sources (educational theory literature and journal articles published between 2021 and 2026). The journal articles were retrieved from Google Scholar, DOAJ, and Sinta-indexed Arabic-education journals. Data were collected through four stages: source identification, classification, analysis, synthesis, and instructional design development, and analyzed using source triangulation, whereby every component of the design is verified against at least three mutually reinforcing references. The findings show that the fourteen functions can be organized into three pyramid layers: the base layer (maf'ūl bih, maf'ūl muṭlaq, maf'ūl lahu, maf'ūl fīh, maf'ūl ma'ah), the middle layer (al-ḥāl, tamyīz, al-mustatsnā, al-munādā), and the top layer (khabar fi'l nāqiṣ, khabar aḥruf, ism inna, ism lā al-nāfiyah li al-jins, al-tābi' li al-manṣūb). This design is grounded in constructivism, Bloom's Taxonomy, and the principle of al-tadrīj, and is complemented by structured learning steps, learning techniques that vary by layer, and a system of formative and summative evaluation.